Pelatihan dan Pendampingan Penyusunan Laporan Keuangan Berbasis Syariah pada Pelaku UMKM Binaan KADIN Kota Bandung: Training and Assistance on the Preparation of Sharia-Based Financial Statements for MSMEs Under the Guidance of KADIN Bandung City - Rozak, Abdul; Minhajuddin, Minhajuddin; Bahri, Khoirun Nisa; Wendiyana, Dhenahi Jerfiani; Damayanti, Rindu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Challenges in financial management, such as the lack of understanding of financial statements, have become a major obstacle to the growth of Micro, Small, and Medium Enterprises (MSMEs). Most MSME actors do not yet grasp the importance of preparing financial statements by Sharia accounting standards, resulting in financial statements that are often made haphazardly without following proper accounting principles. This Community Service Program aims to enhance the capacity of MSMEs under the guidance of the Chamber of Commerce and Industry (KADIN) Bandung in preparing Sharia-based financial statements. The focus of the training includes the introduction of basic Sharia accounting principles, recording transactions in line with Sharia contracts, and preparing financial reports such as income statements, balance sheets, and cash flow statements. Technical assistance is also provided directly to help MSMEs overcome difficulties in implementing a Sharia-based financial system. Survey results indicate that more than 70 percent of MSMEs in Bandung are interested in learning how to prepare Sharia-based financial statements, although they still face challenges in applying the correct methods. This program is expected to offer practical solutions for MSMEs to properly and accurately prepare financial statements by Sharia accounting standards. Moreover, the initiative aims to help MSMEs gain broader access to various Sharia financing institutions and enhance their competitiveness in the era of free trade.